Feather damaging behaviour in adult specimen of scarlet macaw (Ara macao) - Ganem G., Norma (2020)
A case of feather damaging behaviour in a specimen of a scarlet macaw (Ara macao), non-sexed, which entered the Hogar de Paso para Fauna Silvestre of the University of Amazonia on August 24, 2018 is reported. The clinical examination revealed a poor appearance of feathers, with the presence of stress bands in the occipital, temporal, keel, wheelhouse and rower regions. The results of the hemogram, blood chemistry, stool and skin scraping examinations ruled out the presence of bacteria or internal and external parasites as etiology. After the diagnosis of stress feather pecking, a holontological treatment consisting of aromatherapy, homeopathy, therapeutic baths, nutritional balancing and environmental enrichment was established for a period of seven weeks. As a result, a notable improvement was evident, both in the plumage aspect and in the plucking behaviour.